Character Building Through Moral Assistance in Al Amin Al Qur'an Educational Park Salaman Magelang - Milna Wafirah; Titik Zuliyanti (Wahana Islamika: Jurnal Studi Keislaman, 2021)
Character building is crucial in order to prepare a good generation of the nation. There are many ways to instill character formation, one of which is by moral assistance with an Islamic approach. This study aims to analyze the formation of character through the habituation of routine activities carried out at Al Amin Islamic Educational Institute (TPQ), Salaman, Magelang. This study uses qualitative case study method. Moral assistance through routine activities at TPQ Al Amin shows a significant increase in positive character building in children.